Narrating power: Hunting and state formation in Malay and Old Javanese texts—a comparative philological critique - Windayanto, Riqko Nur Ardi; Buduroh, Mamlahatun (Universitas Ahmad Dahlan, 2025)
This study aims to reveal the articulation of state formation as depicted in Hikayat Raja-Raja Pasai and Ādiparwa by examining the hunting events narrated in both texts. By employing the narratology to analyze the events comparatively, this study finds that in the Malay Hikayat, the hunting carried out by Raja Ahmad and Merah Silu (Sultan Maliku’l-Saleh) is incidental, as instead of encountering animal as the primary target, they encounter other objects, directly signifying the formation of a state—namely genealogy and the city/palaces founding as a form of territorialization. Meanwhile, in the Ādiparwa, the hunting is not incidental; the actors do encounter their game (deer), but it results in a curse and death. Nevertheless, hunting articulates genealogy and rituals demonstrating the grandeur of the state. The Malay text originates from the 14th century Sultanate of Samudera-Pasai and was written to justify the relocation of the capital to Pasai for security and defense. In contrast, the Old Javanese text was written in the 10th century under the patronage of Dharmawangśa Tĕguh, aiming to build a myth of descent as a form of political cultural capital. This study contributes to decolonial practice by challenging Geertz's notion that ignores the significance of manuscript. Otherwise, this study sheds light that hunting in the texts is not merely the relation between the king and the game, but discursively also Shapes the political symbol regarding the understanding the historiography of state formation in Southeast Asia. However, as both texts belong to court literature, they tend to reflect elite perspectives and may overlook subaltern voices. Therefore, cross-source analysis and corroboration are necessary to strengthen our understanding of state formation in Indonesia and Southeast Asia.